A Mitochondrial Oxidative Stress Amplifier to Overcome Hypoxia Resistance for Enhanced Photodynamic Therapy. Issue 9 (16th August 2021) - Dong, Ping; Hu, Jialing; Yu, Shuyi; Zhou, Yizhuo; Shi, Tianhui; Zhao, Yun; Wang, Xiuyuan; Liu, Xiaoqing
Abstract: Hypoxia‐induced resistance to tumor treatment restricts further development of photodynamic therapy. Instead of simple reoxygenation to relieve hypoxia in traditional therapeutic approaches, a mitochondria‐targeted reactive oxygen species (ROS) amplifier is constructed to reverse hypoxia resistance and enhance tumor sensitivity to hypoxia‐resistant photodynamic therapy. Mesoporous silica nanoparticles are modified with triphenylphosphine to enhance its blood circulation and endow it with mitochondria‐targeted specificity. α‐Tocopherol succinate and indocyanine green are loaded in mitochondria‐targeted mesoporous silica nanoparticles to reduce innate oxygen consumption by blocking mitochondrial respiration chain, leading to endogenous mitochondrial ROS burst and imaging‐guided photodynamic therapy. This mitochondria‐targeted oxidative stress amplifier not only disrupts mitochondrial redox homeostasis and triggers long‐term high oxidative stress but also makes tumor more sensitive to hypoxia‐resistant photodynamic therapy. The imaging‐guided ROS amplifier confirms the feasibility and effectiveness of both in vitro and in vivo anticancer performance, suggesting a promising clinical strategy in hypoxia‐related tumor treatment. Abstract : A mitochondria‐targeted oxidative stress amplifier is designed to reverse hypoxia resistance and enhance tumor sensitivity to hypoxia‐resistant photodynamic therapy. Oxidative stress amplifiers specifically target mitochondria in tumor cells and block the mitochondrial respiration chain, leading to long‐term high oxidative stress generation as well as full local oxygen availability to enhance hypoxia‐resistant photodynamic therapy.